1985
DOI: 10.1093/nar/13.17.6265
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of a nonsense mutation in mammalian cellsin vivoby the aminoglycoside anthiotics G–418 and paromomycin

Abstract: Aminoglycoside antibiotics in Escherichia coli and yeast can cause ribosomes to read through stop codons during translation. This can result in the phenotypic suppression of nonsense mutations. We show here for the first time that the aminoglycosides G-418 and paromomycin have similar effects in monkey (COS-7) cells in vivo. Suppression of an amber mutation (TAG) by aminoglycosides can restore the activity of a mutant gene transfected into COS-7 cells to almost 20% of wild type levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 11 publications
3
156
0
2
Order By: Relevance
“…However a few patients, often with a milder phenotype, have some detectable ATM protein (3,4). This finding encouraged us to seek compounds, such as aminoglycosides, that have the potential to read through premature termination codons and restore ATM protein function (5,6).…”
mentioning
confidence: 99%
“…However a few patients, often with a milder phenotype, have some detectable ATM protein (3,4). This finding encouraged us to seek compounds, such as aminoglycosides, that have the potential to read through premature termination codons and restore ATM protein function (5,6).…”
mentioning
confidence: 99%
“…Aminoglycoside antibiotics are active in the codonanticodon recognition of aminoacyl tRNAs during translation. 3,29,30 Significantly, 10-20% of the mutations identified in DMD and DMC are nonsense mutations resulting in premature stop codons. 18,21 In the analyses conducted to date, the role of the stop codon nucleotide context on readthrough efficiency has been investigated by directed mutagenesis of target sequences inserted into reporter genes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons indicated an investigation of gentamicin: its effect on readthrough is the best documented to date, and it is known to present a much lower toxicity than other suppressive molecules like G418. 3 Moreover, this antibiotic is currently used in human therapy against bacterial infections, and its pharmacokinetics properties and side effects are well characterized. 17 However, one cannot exclude that a long-term use of gentamicin may induce other types of side effects due to generalized readthrough of normal termination codons.…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycoside antibiotics are able to disrupt translational fidelity in both species. There are now data showing that the growth of mammalian cells in the presence of an aminoglycoside antibiotic can suppress nonsense mutations [148]. In vitro and in vivo studies have suggested that this strategy may be relevant for human diseases.…”
Section: Models Of Dravet Syndromementioning
confidence: 99%